Marketing biofortified crops: Insights from consumer research - Uchitelle-Pierce, Benjamin; Ubomba-Jaswa, Acanda (African Journal of Food, Agriculture, Nutrition and Development, 2017)
As the market for biofortified seed and food grows, farmers increasingly market their excess production to consumers. To develop a global strategy for consumer marketing of biofortified crops, research is needed to understand consumer perceptions, insights, and behaviors around food, agriculture, nutrition and biofortification. Findings from some unpublished research on these topics are reported here. In regions of Nigeria, most farmers and consumers feel positively about biofortification and are interested in consuming a more nutritious diet. In Kampala, Uganda awareness of biofortified vitamin A orange sweet potato is very high, and more than half of survey respondents had purchased it at least once. In Rwanda, farmers and consumers like biofortified high iron beans, but challenges to biofortification include limitations of word-of-mouth communication and the difficulty of obtaining policymaker support for nutrition interventions. The use of behavior change communication and social marketing, tailored to the specific product and market context, can be used to increase awareness and overcome some of these limitations. Several forms of marketing have proven effective in encouraging trial and adoption of biofortified staple crops by farmers and consumers alike.